"Najbolj brane knjige" v slovenskih splošnih knjižnicah - Jager, Petra (Knjižnica, 2008)
The paper investigates hundred most borrowed books in public libraries in perspective of some trends in reading habits and general mission of public libraries. It introduces genres and quality of most borrowed books in Slovenian public libraries. The research was based on one hundred "best read" monographs in Slovenian public libraries during the six year period. The analyzed data from the database conducted since 2002 by Institute of information science include all public libraries which use the COBISS.SI system and have automated borrowing. The "best read" books show big qualitative differences among most borrowed titles. Opposed to few artistic literature titles, the majority of borrowed books are popular literature. The first type of literature represents obligatory reading titles in secondary school system. The list of "best read" books indicates that the majority of users' interests are moving apart from public stategic aims.
Keywords: splošne knjižnice; bralna kultura; branje; knjižne uspešnice; izposoja